HTTP Traffic Simulation and Evaluation for multiple Users in Intranet Network - Christos Bouras; Petros Ganos; E Aravantinos; P Kokkinos (EUROMEDIA-WEBTEC 2002, Modena, Italy, 2002)
In this paper we describe the architecture and design of a network-stressing tool developed to simulate and evaluate the HTTP requests and responses of hundreds of users. There are two major issues that have to be considered when designing and implementing such a simulation tool, the reliability evaluation and the user “friendly” environment. In our application we use a mechanism exploiting Intranet technology to stress the tested network and confirm the performance, proper operation and delay issues. We have also implemented an easy interaction with the user considering the creation of the scenarios and the presentation of the simulation results, pointing out the problems and the network’s status. Finally, we examined through a number of experiments using different simulation scenarios the behavior of the Intranet by load balancing the simulated users.